2022
DOI: 10.3389/fped.2022.894444
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Spectrum, Ethnic and Geographical Distribution of Thalassemia in the Southern Area of Hainan, China

Abstract: BackgroundThalassemia is one of the most common genetic diseases in southern China. Accurate population frequency data regarding the occurrence and distribution of thalassemia are important for designing appropriate prevention strategies for thalassemia. This study aims to reveal the molecular spectrum, ethnic and geographical distribution of thalassemia in the southern area of Hainan Province, China.MethodsA total of 9813 suspected carriers of thalassemia were screened for genetic analysis by using the PCR-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
5
11
0
Order By: Relevance
“…The data of the present study are in line with those of previous studies, and α-thalassemia is the major type of thalassemia in the Li minority ( 14 , 15 ). The proportions of different subtypes of α thalassemia and β-thalassemia are mainly consistent with one recent study carried out in childbearing age adults of the Li minority ( 15 ), particularly for the top two genotypes in α thalassemia (−α 4.2 /αα and −α 3.7 /αα) and top three in β-thalassemia (β CD41–42 /β N , β −28 /β N and β IVS−II−654 /β N ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The data of the present study are in line with those of previous studies, and α-thalassemia is the major type of thalassemia in the Li minority ( 14 , 15 ). The proportions of different subtypes of α thalassemia and β-thalassemia are mainly consistent with one recent study carried out in childbearing age adults of the Li minority ( 15 ), particularly for the top two genotypes in α thalassemia (−α 4.2 /αα and −α 3.7 /αα) and top three in β-thalassemia (β CD41–42 /β N , β −28 /β N and β IVS−II−654 /β N ).…”
Section: Discussionsupporting
confidence: 93%
“…The tradition and economic status of the Li people remain similar due to their concentrated residence. Certain studies have shown that the Li people have a higher prevalence of thalassemia than other minorities (13)(14)(15). However, most studies have been carried out in Li's adults, in whom the genotypes might be different from those of newborns due to survivor bias, which hampers precise and immediate treatment marking and proper prevention policy design.…”
Section: Introductionmentioning
confidence: 99%
“…The top three most common β‐globin mutations in the Zhuhai region were CD41/42 (‐TCTT), IVS‐II‐654 (C>T) and TATAbox‐28, which accounted for 76.30% of all β‐thalassemia mutations. The most common mutation was CD41/42 (‐TCTT), which was consistent with data from Guangdong and several nearby provinces 6,12,13,21,22 . In other provinces, such as Hunan, Yunnan and Fujian, IVS‐II‐654 (C>T) was the most common mutation, whilst CD41/42 (‐TCTT) was the second most common 23,24,25 .…”
Section: Discussionsupporting
confidence: 85%
“…The most common mutation was CD41/42 (-TCTT), which was consistent with data from Guangdong and several nearby provinces. 6,12,13,21,22 In other provinces, such as Hunan, Yunnan and Fujian, IVS-II-654 (C>T) was the most common mutation, whilst CD41/42 (-TCTT) was the second most common. 23,24,25 These studies indicated that the common and widespread mutations were similar across southern China, with diverse frequencies.…”
Section: Hematological Parameters In Thalassemia Carriers Of Differen...mentioning
confidence: 99%
“…β-thalassemia is a group of genetic abnormalities in humans that range from asymptomatic to severe anemia. Southern China has a high incidence of the disease, and the most common mutation for β-thalassemia is CD41/42 (46)(47)(48). There have been case reports of β-thalassemia coexisting with psychiatric diseases in some Mediterranean families.…”
Section: Discussionmentioning
confidence: 99%